UMPSA celebrates Maulidur Rasul and TVET Adventure with Kuala Krau Community - Naqiah, Puaad (UMPSA, 2024)
KUALA KRAU, 11 October 2024 – An-Nur Mosque in Kuala Krau, Temerloh resounded with salutations to the Prophet Muhammad (peace be upon him) during the recent Maulidur Rasul celebration.